EFFICACY OF DIFFERENT ENDODONTIC IRRIGATION PROTOCOLS IN CALCIUM HYDROXIDE REMOVAL - Elka N. Radeva; Desislava M. Tsanova (Journal of IMAB, 2016)
Introduction: Calcium hydroxide is widely used in the field of endodontics as a temporary root canal filling. This medicament significantly increases pH and optimizes the treatment outcome. Its total removal before final obturation is very important. Otherwise it could affect the hermetic filling and respectively the endodontic success. Aim: To evaluate the most effective irrigation protocol of calcium hydroxide removal from root canals. Materials and methods: In this study 36 single root canal teeth were observed. They were randomly divided into three groups (n=10 each group) according to the technique applied for calcium hydroxide removal - manual irrigation, irrigation and Revo-S rotary instrumentation; and passive ultrasonic irrigation, and a control group (n=6) – irrigation with distilled water only. After calcium hydroxide removals following the procedures above, teeth were separated longitudinally in a buccal-lingual direction and remnants of medicaments were observed in the apical, middle and coronal part of each tooth. Then all of the specimens were observed using scanning electron microscopy and evaluated by a specified scale. The results have undergone statistical analysis. Results: In the case of calcium hydroxide in the apex and in the middle with highest average is Revo-S, followed by Ultrasonic and irrigation. In the coronal part the highest average belongs to Revo-S, irrigation and Ultrasonic. In all groups the highest average is represented by control group. Conclusion: There is not a universal technique for removal of intracanal medicaments and applying more than one protocol is required.